Scripting Gender Through Cinema: Analysis Of Indigenized Cinematic Shakespearean Adaptation’s Trailer (Journal of Namibian Studies : History Politics Culture, 2023)
In the process of ‘identity’ assimilation in an individual, references of the society around and the rules, norms to be learnt and internalized play a predominant role. Cinema is one of the largely viewed mass media platform for the Indian audience. Cinema with its intriguing quality of creating a society along with the narratives has been widely studied by researchers in influencing the constructed world around. The trailers are essential to the reception of cinema. Hence, trailers are made accessible for public view to a larger extent to advertise the film. This quality of the trailers makes it a fertile platform for research into the society, cinema propagates as accepted. This paper mainly focusses on Shakespeare cinematic adaptation trailers by Vishal Bharadwaj Maqbool (2003), Omkara (2006) and Haider (2014). The research concentrates on the ‘masculinity’ the trailers surreptitiously imbibe and in turn advertise to the viewers.